Activation of TnSmu1, an integrative and conjugative element, by an ImmR-like transcriptional regulator in Streptococcus mutans. Issue 10 (6th October 2022) - King, Shawn; Quick, Allison; King, Kalee; Walker, Alejandro R.; Shields, Robert C.
Abstract : Integrative and conjugative elements (ICEs) are chromosomally encoded mobile genetic elements that can transfer DNA between bacterial strains. Recently, as part of efforts to determine hypothetical gene functions, we have discovered an important regulatory module encoded on an ICE known as TnSmu1 on the Streptococcus mutans chromosome. The regulatory module consists of a cI-like repressor with a helix-turn-helix DNA binding domain immR Smu (immunity repressor) and a metalloprotease immA Smu (anti-repressor). It is not possible to create an in-frame deletion mutant of immR Smu and repression of immR Smu with CRISPRi (CRISPR interference) causes substantial cell defects. We used a bypass of essentiality (BoE) screen to discover genes that allow deletion of the regulatory module. This revealed that conjugation genes, located within TnSmu1, can restore the viability of an immR Smu mutant. Deletion of immR Smu also leads to production of a circular intermediate form of TnSmu1, which is also inducible by the genotoxic agent mitomycin C. To gain further insights into potential regulation of TnSmu1 by ImmRSmu and broader effects on S. mutans UA159 physiology, we used CRISPRi and RNA-seq. Strongly induced genes included all the TnSmu1 mobile element, genes involved in amino acid metabolism, transport systems and a type I-C CRISPR-Cas system. Lastly, bioinformatic analysis shows that the TnSmu1 mobile element and its associated genes are well distributed across S. mutans isolates. Taken together, our results show that activation of TnSmu1 is controlled by the immRA Smu module, and that activation is deleterious to S. mutans, highlighting the complex interplay between mobile elements and their host.